Evaluating the Impact of Service Quality and Trust on Customer Loyalty in Financial Institutions - Rapita, Rapita; Gunarto, Muji; Helmi, Sulaiman; Elpanso, Efan (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study was conducted at PT. Permodalan Nasional Madani (PNM) Unit Ilir Timur 2-2 Palembang to measure the effect of service quality and trust on customer satisfaction and its impact on customer loyalty. The background of this study is based on the rapid economic development in Indonesia, which drives an increase in the financial needs of the community, making the role of financing institutions increasingly important. The purpose of this study is to explore how service quality, trust, and satisfaction affect customer loyalty. The method used is a quantitative method with a positivistic approach, utilizing multiple linear regression analysis. Data were obtained from 100 respondents selected using purposive sampling techniques. The results of the study indicate that service quality has a significant effect on customer loyalty, with a regression coefficient of 0.763 and a significance value of 0.000. However, customer trust and customer satisfaction do not show a significant effect on loyalty in this model. Therefore, it is recommended that PT. PNM focuses more on improving service quality to strengthen customer loyalty, while trust and satisfaction should still be considered through a more specific approach and measurement. The study concludes that although service quality is a major factor in building loyalty, it is important for companies not to ignore the role of trust and satisfaction in the long term